Genetic Association Studies of Suicidal Behavior: A Review of the Past 10 Years, Progress, Limitations, and Future Directions - Mirkovic, Bojan; Laurent, Claudine; Podlipski, Marc-Antoine; Frebourg, Thierry; Cohen, David; Gerardin, Priscille (Frontiers in Psychiatry, 2016)
Suicidal behaviours, which range from suicidal ideation to suicide attempts and completed suicide, represent a fatal dimension of mental ill-health. The involvement of genetic risk factors in suicidal behaviour is supported by family, twin, and adoption studies. The aim of this paper is to review recent genetic association studies in suicidal behaviours including (i) case-control studies, (ii) family-based association studies and (iii) genome-wide association studies (GWAS). Various studies on genetic associations have tended to suggest that a number of genes (e.g., tryptophan hydroxylase, serotonin receptors and transporters or brain-derived neurotrophic factors) are linked to suicidal behaviours, but these findings are not consistently supported by the results obtained. Although the candidate-gene approach is useful, it is hampered by the present state of knowledge concerning the pathophysiology of diseases. Interpretations of GWAS results are mostly hindered by a lack of annotation describing the functions of most variation throughout the genome. Association studies have addressed a wide range of SNPs in numerous genes. We have included 104 such studies, of which 10 are family-based association studies and 11 are GWAS studies. Numerous meta-analyses of case-control studies have shown significant associations of suicidal behaviour with variants in the serotonin transporter gene (5-HTT or SLC6A4) and the tryptophane hydroxylase1 gene (TPH1), but others report contradictory results. The gene encoding brain-derived neurotrophic factor (BDNF) and its receptor (NTRK2) are also promising candidates. Only two of the GWAS studies showed any significant associations. Several pathways are mentioned in an attempt to understand the lack of reproducibility and the disappointing results. Consequently, we review and discuss here the following aspects: (i) sample characteristics and confounding factors; (ii) statistical limits; (iii) gene-gene interactions; (iv) gene, environment and by time interactions; and (v) technological and theoretical limits. Keywords: association study, genetics of suicide, suicidal behaviour, single nucleotide polymorphism